3(5 - x) - 3(1 - 2x) = 42 Resolver a Equaçao!!
Soluções para a tarefa
Respondido por
1
Eu pensei da seguinte forma:
3(5-x) - 3(1-2x) = 42
15 - 3x - 3 + 6x = 42
-3x + 6x = 42 + 3 - 15
3x = 30
x = 30÷3
x= 10
10
3(5-x) - 3(1-2x) = 42
15 - 3x - 3 + 6x = 42
-3x + 6x = 42 + 3 - 15
3x = 30
x = 30÷3
x= 10
10
Respondido por
2
15 - 3x - 3 + 6x = 42
-3x + 6x = 42 - 15 + 3
3x = 30
x = 30 ÷ 3
x = 10
-3x + 6x = 42 - 15 + 3
3x = 30
x = 30 ÷ 3
x = 10
Perguntas interessantes
Ed. Física,
11 meses atrás
Geografia,
11 meses atrás
Contabilidade,
11 meses atrás
História,
1 ano atrás
Administração,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
História,
1 ano atrás